USE OF NUMBERED HEAD TOGETHER MODEL IN INCREASING ISLAMIC EDUCATION LEARNING INTERESTSTUDENTS IN CLASS VII SMPN 07 NORTH BENGKULU - Basinun Basinun (Universitas Islam Negeri Fatmawati Sukarno, 2018)
Problem identification of this research is 1. Still low student interest which caused by Lack of attention of stu- dent to learning of PAI especially in subject matter closer to Allah SWT. Its very beautiful name, like students often jok- ing, often daydreaming and students often out of the classroom. 2. the method used is always monoton that the teacher always use the lecture method, so that students feel bored in teaching and learning process (PBM). The approach used in this is a classroom action research, which will be carried out through a few steps until the research is successful. The results obtained on the prasiklus step the number of values obtained is 453 with the result of the average value of 17.42 with 43.55% percentage, from the observation proves that the lack of interest in learning students in learning PAI es- pecially the subject matter closer to the god SWT .The very beautiful name with the value category is still low, because the value obtained in the observation is still below the KKM. Because the value obtained is low, therefore the next step needs to be done, so that the results achieved can be maximized.The next step is cycle I with the total value of 591 with the result of the average value of 22,73 result of the percentage of 56,82% from result of observation prove that student have interest but student interest of student have not show in full, and value obtained in observation still below KKM . Because the results obtained are still not maximal then need to re-implement the next step, so that the results achieved can be maximized. The second step of cycle II with the total value of 731 and the results of the average value of 28.11 with the percentage of 70.27%, And the results of students already interested but the student’s learning interest has not shown fully, given the value obtained in the observation is still less and still below KKM. Therefore, it is necessary to implement the next step, so that the results achieved can be maximized. Step cycle III the number of values obtained is 837 with an average value of 32.19 and the percentage is 80.47%. From the observations made through the observa- tion sheet proves that in the step of cycle III students already seen if they are very interested in learning and the value obtained is already above the minimum completeness criteria (KKM) that have been determined. Because the results obtained are satisfactory, the action research is stopped, just until the third cycle. From the results of the above research proves that by using NHT method can increase student learning interest in learning PAI